OPTIMIZING ASN TALENT DEVELOPMENT WITH HUMAN CAPITAL MANAGEMENT - R. Taqwaty Firdausijah (Jurnal Multidisiplin Sahombu, 2022)
Human capital management is a strategic approach in human resource management that focuses on increasing the value and effectiveness of individuals in organizations. In the context of public services, improving the quality and competence of ASN is a key factor in achieving efficient and responsive government performance. However, many government agencies face challenges in identifying and developing the potential of existing ASNs, as well as facing dynamic changes in societal demands and organizational needs. This study aims to investigate and analyze optimal ways of developing and utilizing the potential and skills of the state civil apparatus (ASN) through a human capital management approach. This research uses a qualitative approach with descriptive methods. The research results show The results of the study show that the application of the concept of Human Capital Management (HCM) in the development of ASN in a planned and structured manner has a positive impact on organizational performance and public services. Through identification of individual potential and competencies, as well as appropriate coaching and mentoring, ASNs are able to improve their professionalism and adaptability in dealing with changes in the work environment. The use of information and communication technology (ICT) also contributes to increasing collaboration, efficiency and innovation within organizations. The merit system implemented in performance management provides incentives for ASN to work more productively and have superior performance. In addition, a positive and inclusive organizational culture creates an inspiring work environment and supports the growth of ASN.